Uncertainties in Long-Term Twenty-First Century Process-Based Coastal Sea-Level Projections - van de Wal, R. S. W.; Zhang, X.; Minobe, S.; Jevrejeva, S.; Riva, R. E. M.; Little, C.; Richter, K.; Palmer, M. D. (Surveys in geophysics, 2019)
Many processes affect sea level near the coast. In this paper, we discuss the major uncertainties in coastal sea-level projections from a process-based perspective, at different spatial and temporal scales, and provide an outlook on how these uncertainties may be reduced. Uncertainty in centennial global sea-level rise is dominated by the ice sheet contributions. Geographical variations in projected sea-level change arise mainly from dynamical patterns in the ocean response and other geophysical processes. Finally, the uncertainties in the short-duration extreme sea-level events are controlled by near coastal processes, storms and tides.